Análisis de frontera estocástica aplicado a medir la eficiencia en riesgo de la banca mundial : impacto de las medidas y regulaciones del sector bancario (2017)
The subject addressed in this paper refers to the analysis of the relative efficiencies at risk of banking entities worldwide in the period between 2003 and 2015 using stochastic frontier analysis and, additionally, seeks to understand the relationship and impact of regulatory and supervisory measures that have been adopted in each country in recent years. The study found that the regulations have an opposite effect and increase the risks assumed by the entities of the world banking. Finally, it is presented a comparison between the efficiencies in market, capital and credit risk.